2010
DOI: 10.1158/1541-7786.mcr-10-0225
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and the Complement Cascade

Abstract: Despite significant research on the role of inflammation and immunosurveillance in the immunologic microenvironment of tumors, little attention has been given to the oncogenic capabilities of the complement cascade. The recent finding that complement may contribute to tumor growth suggests an insidious relationship between complement and cancer, especially in light of evidence that complement facilitates cellular proliferation and regeneration. We address the hypothesis that complement proteins promote carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
249
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(265 citation statements)
references
References 160 publications
6
249
0
3
Order By: Relevance
“…40,41 Besides regulation of the coagulation system, complement proteins stimulate cancer invasion through enhanced EMT, degradation of ECM by proteases such as MMP-9 and induction of chemotactic stimuli and growth factors. [42][43][44] CFD is essential for alternative pathway activation and was found to be identical to the adipokine adipsin which is expressed in monocytes/macrophages. 45,46 Since the CTC lines were established from patients with advanced SCLC characterized by large number of these cells in the circulation, CFD may be involved in cancer-associated weight loss.…”
Section: Secretory Phenotype Of Sclc Ctc-induced Macrophagesmentioning
confidence: 99%
“…40,41 Besides regulation of the coagulation system, complement proteins stimulate cancer invasion through enhanced EMT, degradation of ECM by proteases such as MMP-9 and induction of chemotactic stimuli and growth factors. [42][43][44] CFD is essential for alternative pathway activation and was found to be identical to the adipokine adipsin which is expressed in monocytes/macrophages. 45,46 Since the CTC lines were established from patients with advanced SCLC characterized by large number of these cells in the circulation, CFD may be involved in cancer-associated weight loss.…”
Section: Secretory Phenotype Of Sclc Ctc-induced Macrophagesmentioning
confidence: 99%
“…Mice deficient in C3 also exhibited significantly decreased tumor proliferation compared to wild-type mice (Markiewski et al, 2008). In another study, a cleavage product of complement C3, C3a was found to demonstrate proliferative activities and increase activation of proteins whose overexpression has been strongly associated with neoplasia (Rutkowski et al, 2010;Vivanco & Sawyers, 2002). Other tumorigenic effects of C3 include production of www.ccsenet.org/cco Cancer and Clinical Oncology Vol.…”
Section: Complement C3mentioning
confidence: 99%
“…Huang, Wang, Zhang, Li, & Li, 2013) Anastellin 256 (Neskey, Ambesi, Pumiglia, & McKeown-Longo, 2008;Pasqualini, Bourdoulous, Koivunen, Woods, & Ruoslahti, 1996;M. Yi & Ruoslahti, 2001) Apolipoprotein A-1 31 (Macuks et al, 2010;Zamanian-Daryoush et al, 2013) Fibrinogen β chain 56 (Krajewska et al, 2010) Keratin type I cytoskeletal 9 62 (W. Yi et al, 2013) Others: Complement component C4b (Childo blood group) 193 (Markiewski & Lambris, 2009;Rutkowski et al, 2010) …”
Section: Biochemical and Immunological Characterizations Of Ca215-s+ mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the three initiator pathways that activate the complement system, our cancer profile suggests that the initiators involved with the alternate complement pathway are diminished, while the terminal C5 remains unaltered. Though its role in cancer is complex and remains inconclusive, activated complement component proteins are abundantly dispersed throughout the inflammatory tumor microenvironment [19]. Finally, there is overwhelming suggestion in the literature that induction of complement is beneficial for targeted monoclonal antibody cancer therapy [20].…”
Section: Coagulation and Complement Cascadementioning
confidence: 99%